The balance of canopy and soil effects determines intraspecific differences in foundation species' effects on associated plants. (12th June 2018) - Pistón, Nuria; Michalet, Richard; Schöb, Christian; Macek, Petr; Armas, Cristina; Pugnaire, Francisco I.
Abstract: The impact of plant–plant interactions on species diversity patterns has been broadly addressed in stressful environments, such as alpine ecosystems, where foundation species promote species richness by creating habitat for other species. However, foundation species with contrasting phenotypes might modify the microhabitat differently, which would alter the subordinate community composition, and coincide with distinct feedback effects of those subordinate species on the foundation species. However, the precise interaction mechanisms that facilitate species are not fully understood, especially the relative contribution of above‐ and below‐ground compartments of foundation species to subordinate species and the potential feedbacks they receive. We explored whether two contrasted canopy phenotypes (tight and loose) of the shrub Cytisus galianoi differed in their effects on the microhabitat and on subordinate plant community composition in a dry subalpine system. We also experimentally distinguished the relative contribution of above‐ (canopy) and below‐ground (soil) effects of C. galianoi on the most frequent subordinate species, Festuca indigesta, as well as the reciprocal effects of F. indigesta on C. galianoi . We performed observational and manipulative experiments to assess the influence of phenotypic differences of the shrub on understorey microhabitat and subordinate plant community composition. Reciprocal effects were assessed by removing either F. indigesta from the understorey of the two shrub phenotypes or the C. galianoi canopy from the immediate vicinity of F. indigesta . The two C. galianoi phenotypes differed in mean values of functional traits (like stem density or plant height), modified their understorey microhabitats differently and hosted distinct subordinate communities. Loose phenotypes had more positive effects on community composition and diversity than tight phenotypes. In addition, tight phenotypes simultaneously showed both more positive above‐ground and more negative below‐ground effects on F. indigesta than loose phenotypes. There were no significant feedback effects of F. indigesta on C. galianoi . The two phenotypes of the foundation species C. galianoi showed contrasting effects on the subordinate plant community: Compared to the tight phenotype, the loose phenotype had higher associated species diversity and reduced reciprocal interaction intensities above‐ and below‐ground with the subordinate species F. indigesta . This highlights the impact of phenotypic variation for plant interactions and community‐level diversity. A plain language summary is available for this article. Abstract : Plain Language Summary Foreign Language Abstract Resumen: El impacto de las interacciones planta‐planta en los patrones de diversidad de especies se ha abordado ampliamente en ambientes severos, como los ecosistemas alpinos, donde las especies fundadoras promueven la riqueza de especies creando hábitats para otras especizes. Sin embargo, las especies fundadoras con fenotipos contrastantes podrían modificar el microhábitat de manera diferente, lo que alteraría tanto la composición de la comunidad de especies subordinadas como los efectos recíprocos de esas especies subordinadas a las especies fundadoras. Sin embargo, los mecanismos de facilitación aún no se comprenden en su totalidad, especialmente la contribución relativa de la parte aérea y la parte bajo tierra de las especies fundadoras y los efectos recíprocos que reciben por parte de las especies subordinadas. En este estudio exploramos si dos fenotipos de copa (densa vs. abierta) del arbusto Cytisus galianoi difieren en sus efectos sobre el microhábitat y sobre la composición de la comunidad de plantas subordinadas en un sistema subalpino seco. También estudiamos experimentalmente la contribución relativa de los efectos de la parte aérea de C. galianoi (copa) y la parte debajo del suelo (suelo) en la especies subordinada más frecuente, Festuca indigesta, así como los efectos recíprocos de F. indigesta sobre C. galianoi . Realizamos tanto un muestreo observacional como experimentos de manipulación para evaluar la influencia de los diferentes fenotipos del arbusto en el microhábitat y la composición de la comunidad vegetal subordinada. Los efectos recíprocos se evaluaron eliminando F. indigesta bajo las copas de los dos fenotipos de arbustos y eliminando parte de la copa de C. galianoi alrededor de F. indigesta . Ambos fenotipos de C. galianoi se diferenciaron en los valores medios de los rasgos funcionales (como la densidad del tallo o la altura de la planta), modificaron sus microhábitats bajo las copas de manera diferente y albergaron distintas comunidades de subordinadas. Los fenotipos abiertos ejercieron un efecto positivo mayor sobre la composición de la comunidad y la diversidad que los fenotipos densos. Además, los fenotipos densos mostraron tanto un efecto positivo de copa mayor como un efecto negativo de suelo mayor sobre F. indigesta comparado con el fenotipo abierto. No hubo efectos recíprocos significativos de F. indigesta sobre C. galianoi . Los dos fenotipos de la especie fundadora C. galianoi mostraron efectos contrastantes en la comunidad de plantas subordinadas: en comparación con el fenotipo denso, el fenotipo abierto tenía una mayor diversidad de especies asociadas y una intensidad de interacción de copa y suelo sobre F. indigesta menor. Nuestros resultados destacan el impacto de la variación fenotípica en las interacciones entre plantas y en la diversidad a nivel de comunidad.